SET-UP AND APPLICATION OF BIOTECHNOLOGICAL METHODS IN AVIAN FIELD - G. Manarolla (Università degli Studi di Milano, 2013)
The use of biotechnology in avian field has been increased in the last decade especially on the track of the complete sequencing of chicken genome and on the global threat of avian flu pandemic which alerted the scientific community worldwide. Nevertheless, it is still on the whole a minor and spotty approach in avian field. Matter-of-factly, birds can be roughly divided into two groups on a research point of view: poultry and non-poultry (companion and wild birds). The economic impact of the latter is usually scarce if compared to the former and to other veterinary and human contexts. Thus, routine use of laboratory diagnostic tools including biotechnological methods is usually limited to the more expensive psittacines species (i.e. DNA-based determination of sex, diagnosis of chlamydiosis etc.) or to endangered species. As for poultry, extensive use of biotechnology is performed in vaccine research and genetic selection with a secondary role in avian and comparative pathology. Besides, chicken has historically assumed the role of avian model. Consequently, birds are often considered an uniform class but they are not, and a deep knowledge of the huge diversity which can exist among the several avian species is fundamental to correctly approach and interpret avian research no matter using biotechnology or not. For all these reasons it seemed an unique occasion to match the documented experience and activity in avian field (acquired during a previous doctorate) to biotechnological methods as the subject of this doctoral thesis. After a brief introduction revising fundamental principles of the molecular methods used, this thesis is divided into two parts. The first is focused on avian immunity and in particular on the TIR8-SIGIRR receptor which has been thoroughly investigate in chickens as a model for avian species and with an importance in itself as an ubiquitously diffused food production animal. The second part is made up of some diagnostic challenges arisen during the routine diagnostic activity of the ...